БАСЛАЎЫШ КЛАСС ОҚЫЎШЫЛАРЫН ӘДЕП-ИКРАМЛЫЛЫҚҚА ТӘРБИЯЛАЎДА ХАЛЫҚ АЎЫЗЕКИ ДӨРЕТПЕЛЕРИНИҢ ТУТҚАН ОРНЫ - Ихласов, У.; Ихласов, И. (ILIM hám JÁMIYET, 2017)
The article deals with methods of upbringing the pupils of primary schools in the spirit of moral stability on the basis of folklore works. As the authors point out, from the early periods of human society our ancestors paid much attention to moral and aesthetic upbringing of young generation, to bring up in them the high qualities of humanity. They were reflected in everyday behaviour in the family and social customs and rituals, and they are brightly depicted in the folk works and have reached our times becoming the basic points of the moral education of generations. The authors consider these properties as an organical part of the educational process of the young generation.